2019
DOI: 10.3389/fpsyg.2019.00215
|View full text |Cite
|
Sign up to set email alerts
|

Forget the Folk: Moral Responsibility Preservation Motives and Other Conditions for Compatibilism

Abstract: For years, experimental philosophers have attempted to discern whether laypeople find free will compatible with a scientifically deterministic understanding of the universe, yet no consensus has emerged. The present work provides one potential explanation for these discrepant findings: People are strongly motivated to preserve free will and moral responsibility, and thus do not have stable, logically rigorous notions of free will. Seven studies support this hypothesis by demonstrating that a variety of logical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 71 publications
7
31
0
Order By: Relevance
“…Implications and Directions for Future Research The findings reported in this paper have theoretical implications for both the psychology of free will belief and political psychology. First, these findings provide further and more direct support for previous work conducted on free will belief as motivated social cognition (Clark, Baumeister, et al, 2017;Clark et al, 2014;Clark, Shniderman, et al, 2018;Clark, Winegard, & Baumeister, 2019;Vonasch et al, 2017). The work reported here demonstrates that belief in free will is linked to a desire to hold people accountable for their moral wrongdoing, and that free will attributions vary as a function of the valence of the action, how moral or immoral it is perceived to be, and even who the target is.…”
Section: Overview Of Findingssupporting
confidence: 81%
See 2 more Smart Citations
“…Implications and Directions for Future Research The findings reported in this paper have theoretical implications for both the psychology of free will belief and political psychology. First, these findings provide further and more direct support for previous work conducted on free will belief as motivated social cognition (Clark, Baumeister, et al, 2017;Clark et al, 2014;Clark, Shniderman, et al, 2018;Clark, Winegard, & Baumeister, 2019;Vonasch et al, 2017). The work reported here demonstrates that belief in free will is linked to a desire to hold people accountable for their moral wrongdoing, and that free will attributions vary as a function of the valence of the action, how moral or immoral it is perceived to be, and even who the target is.…”
Section: Overview Of Findingssupporting
confidence: 81%
“…In moral reasoning, desires to blame and to hold individuals morally responsible compel people to produce rational explanations that would justify their moral judgments (Alicke, 2000;Clark et al, 2015). Indeed, a growing body of research has demonstrated that the desire to hold individuals morally accountable for their immoral behaviors can lead to motivated judgments that such immoral behaviors are intended, under the agent's control, and freely chosen (Alicke, 1992(Alicke, , 2000Alicke, Rose, & Bloom, 2011;Clark et al, 2014;Clark, Bauman, Kamble, & Knowles, 2017;Clark, Winegard, & Baumeister, 2019;Cushman, Knobe, & Sinnott-Armstrong, 2008;Hamlin & Baron, 2014;Knobe, 2003;Knobe & Fraser, 2008;Leslie, Knobe, & Cohen, 2006;Phillips & Knobe, 2009).…”
Section: Motivated Beliefs In Free Willmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these two limitations, we believe that we have made a valuable contribution to the literature by problematizing two key pieces of evidence that have been used to bolster natural compatibilism. When considered against the backdrop of the extant research that suggests either that incompatibilism is the default view or that compatibilist intuitions are driven by epistemically problematic psychological processes like performance errors, motivated cognition, affective bias, intrusion effects, and the like (Clark, Winegard, & Baumeister, 2019;Feltz et al, 2009;Feltz & Millan 2013;Nadelhoffer et al, 2014;Nadelhoffer et al, 2019a;2019b;Nichols & Knobe 2007;Rose, 2019;Rose, forthcoming;Rose et al, 2016;Roskies & Nichols, 2008;Sarkissian et al, 2010;Wisniewski et al, 2019), our findings further complicate the project of compatibilists who want to align their view with common sense. This is not to say that the case is closed when it comes to natural compatibilism (see for example Turri, 2017a;2017b).…”
Section: % 52%mentioning
confidence: 69%
“…In future work, we could strengthen the case for the source‐paradox solution by arguing that resistance to the source paradox may be due to motivated reasoning. For instance, recent research in experimental philosophy suggests that people—and perhaps philosophers even more so (due the “paradox of expertise”)—respond in a biased way to arguments against the existence of free will and moral responsibility because they do not want to accept that conclusion (Clark et al ).…”
Section: The Paradox Of Moral Luckmentioning
confidence: 99%